Pengaruh Curah Hujan Dan Hari Hujan Terhadap Produksi Tebu ( Saccharum officinarum Linn ) Di Kebun Kwala Bingai PT.Perkebunan Nusantara II - Mulia Frans G. S; Irsal Irsal; Emmy Harso Kardhinata (Jurnal Agroekoteknologi, 2015)
The climate factors is very influental to the growth and productivity of sugarcane. Rainfall is an important climatic element observed. The purpose of this reseach was to determine the effect of rainfall and rainy day as well as the correlation of both on sugarcane yield. This research was held at PTPN II Unit Kwala Bingai District Langkat Province of North Sumatera from Mey 2015 to Agustus 2015. The primary data for analytical purposes include sugarcane production; rainfall; and rainy days in 2009, 2010, 2011, 2012, 2013 at 6 locations. The result showed that rainfall and rainy days had not give contribution to sugarcane production. Based on regresion analysis at α = 0,05 rainfall as well as rainy days have low correlation to sugarcane yield.Keywords: rain fall, rain day, production of sugar cane.